A multi-centre evaluation of multiple supernumerary premolar prevalence - Gunduz Kaan; Avsever Hakan; Orhan Kaan; Canıtezer Gözde; Acikgoz Aydan; Oz Ulas; Midilli Muhammet (Sciendo, 2015)
The occurrence of multiple supernumerary teeth is rare and often found in association with syndromes such as cleidocranial dysplasia, Gardner's syndrome or cleft lip and palate. Few examples of non-syndromal multiple supernumerary teeth have been reported. The aim of this multi-centre study was to investigate the prevalence of supernumerary premolar teeth in non-syndromic patients and to investigate the association between the presence of supernumerary premolar teeth and malocclusion type in a Turkish population.